HILARY BROWN, Women and Early Modern Cultures of Translation: Beyond the Female Tradition, Oxford 2022, Oxford University Press, 301 s., ISBN 9780192844347 - Eichlová Ördöghová, Gabriela (Dějiny – teorie – kritika, 2023)
Book review